The Harmony between the Self, the Other and the Cosmos as a Rule. The Constitutionalization of Traditional Culture in Andean Countries and in a Comparative Perspective - Bagni, Silvia (Governare la paura. Journal of interdisciplinary studies, 2013)
The Law has always been an instrument to exorcise different kinds of fear, primarily the fear of differences, through the distribution of shares of power. Perhaps, this system, inherently conflictual, is behind the failure of the multicultural policies of many countries, that have divided the society in as many separate communities as are the elements that differentiate each human being. The Law has also recognized to men a total power over Nature, feeding its illusion of control, that in recent decades has shattered in front of several natural disasters. Ecuador, Buthan and South Africa have introduced in their Constitutions ideas belonging to the indigenous cultural tradition (buen vivir, buddhism and ubuntu), which express harmony between men and Nature. The paper analyzes these experiences in order to propose a new model of eco-friendly constitutionalism.